Implementasi Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah pada UMKM Aifa Coffeeshop - hafidz, muhammad (Jurnal KIAFE, 2024)
This study examines the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in the preparation of financial statements at Aifa Coffeeshop. The study employs a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation. The results show that Aifa Coffeeshop still uses a very simple financial recording system and has not prepared its financial statements in accordance with SAK EMKM. This condition is mainly caused by the management’s limited knowledge of the applicable financial accounting standards and the lack of government outreach regarding the preparation of financial statements based on SAK EMKM. The findings indicate that Aifa Coffeeshop requires greater accounting knowledge and practical guidance to prepare more complete, structured, and standardized financial reports.